The Generalship of P. Quinctilius Varus in the Clades Variana. (2019) - Morgan, Daniel
Abstract: The clades Variana was a major Roman defeat, occurring over three days of fighting in AD 9. Three Roman legions and several units of auxiliaries were destroyed, and their commander, Publius Quinctilius Varus, died at the climax of the fighting. Suetonius said that the army paid the price for its general's temeritas and neglegentia, and many other commentators, both ancient and modern, have condemned Varus as a general ever since. This paper re-evaluates Varus' competence as a general by re-examining the extensive literary and archaeological evidence for the clades, with reference to comparative literary evidence that shows how Roman generals usually reacted in comparable situations. It will be argued that Varus' aggressive march towards a rumoured rebellion with a large baggage train, his re-organisation of the baggage train, his change of course westwards, and even his fatal advance into the defile at Kalkriese, were logical decisions in the context of standard Roman military responses to crisis. It is shown that Varus was hamstrung by intelligence and logistical limitations that were not peculiar to him but were systemic to the Roman army at the time. Varus' generalship is thus contextualised as relatively competent, although uninspired.